The Evidence Of Seal Breaking Or Safety Sign In Crime Of Customs - Rustam Hs Akili; Roy Marthen Moonti; Sulfadli Aliah (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this study is to find out the proof of damage to seals or security signs in customs crimes at Gorontalo customs and excise office and to find out what factors influence the proof of damage to seals in customs crimes at Gorontalo customs and excise office. Implementation This research is doctrinal legal research, namely research that provides systematic exposure to regulations governing certain legal categories, analyzes the relationship between regulations, explains areas that experience obstacles, and predicts future developments. The forms of proof of the crime of destroying the seal or security sign in the customs sector can be carried out by importers, exporters, law enforcement officers, entrepreneurs managing customs services, by legal entities, and individuals. Customs crimes can cause losses to the state, so prevention and law enforcement efforts, especially the application of criminal sanctions, are a means that can prevent and eradicate customs crimes. To prevent the occurrence of other forms of criminal acts in the customs sector, especially the destruction of security seals/signs, it is necessary to coordinate and cooperate between government agencies and law enforcement officers as well as the community to carry out supervision in the form of monitoring all customs activities and evaluating and reporting and taking action if there are activities. which violates Law Number 17 of 2006 concerning Amendments to Law Number 10 of 1995 concerning Customs. For the Government to establish a special prison or detention center for perpetrators of the crime of breaking the security seal in Gorontalo province at the Customs and Excise Office of Gorontalo, to facilitate the investigation process. And without the participation of the community, law enforcement will not be achieved optimally, public awareness to obey the law is very much needed and increases the role model for the community itself